(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The present work validates the home range technique (AH) for the lizard Stenocercus iridescens, as a case of study for the saurian conservation in dry forests of southwestern Ecuador. The field phase was achieved in Cerro Blanco Protected Forest, during January-March 2016. A plot of 7.5 ha was delimited, individuals of S. iridescens were captured, marked, measured, georeferenced and released; those individuals were monitored twice a week at different times of day, the minimum number of relocations per individual was four. AH size was estimated through the minimum convex polygon (MCP) by QGIS 2.8 software. We got data from 20 subjects (♂ = 10, ♀ = 10), where AH was 21 m2 (± 1.92), and a significant positive correlation between the AH and the total length (LT) of individuals (r2 = 0.8) were obtained without distinction of sex. These results demonstrate that this technique is feasible, economical, fast, effective, and contributes to the knowledge of the ecological niche of the species. It is suggested to replicate similar studies in species endemic to dry forests as Microlopus occipitalis, M. peruvianus, Dicrodon guttulatum and Stenocercus puyango, and also for those that have been assigned to some threat category, as Callopistes flavipunctatus (EN).